Influence of Concentrated Infiltration on Soil N, P, Organic Carbon and Heavy Metals in Urban Rain Gardens - Guo Chao; Xie Xiao; Li Jiake (Shuitu baochi tongbao)
[Objective] The influence of concentrated infiltration from rainfall runoff on soil of rain gardens in Xi'an City, Shaanxi Province was studied in order to provide a scientific reference for the reasonable configuration and application of concentrated infiltration technology of urban rainfall runoff. [Methods] Runoff data from two rain garden treatments (RD1: accepting roof rainfall runoff; RD2: accepting roof and road rainfall runoff) was acquired from 8—9 years on the campus of Xi'an University of Technology. From 2016 to 2018, 16—18 rainfall events were monitored to determine the pollutant load of chemical oxygen demand (COD), total suspended solids (TSS), N, P, and the event mean concentration (EMC) of heavy metals in the rainfall runoff of the two rain gardens. From April 2017 to February 2019, a total of seven soil samples at different soil depths in the two gardens were collected to determine NH4-N, NO3-N, TN, TP, total organic carbon (TOC), and heavy metals (Cu, Zn, and Cd) to assess the vertical distribution of N, P, TOC, and heavy metal contents in the rain garden soils. [Results] The EMC concentrations of COD, TSS, NH4-N, TN, and TP in RD1 were all greater than those in RD2, but opposite results were obtained with regard to heavy metals. The contents of NH4-N and TN showed a gradually decreasing trend with soil depth. However, the contents of NO3-N and TP in the soil gradually increased with soil depth, and they were all greater below 50 cm than the contents in the upper layer (0—50 cm). The TOC content in the rain garden soil showed a gradually decreasing trend with soil depth. Heavy metal contents were large in the 0—30 cm soil layer. Cu and Zn mainly existed in the form of iron-manganese oxide bound state and residue state, while Cd mainly existed in the form of exchangeable and carbonate-bound forms. The contents of Cu, Zn, and Cd in rain garden soil had good relationships with TOC (R2>0.8). [Conclusion] Concentrated infiltration in rain gardens had a clear influence on soil N, P, and heavy metals. NO3-N and TP leaching occurred in rain garden soil. The contents of NH4-N and TN in rain garden soil were mainly concentrated in the 0—50 cm soil layer, while heavy metals were mainly concentrated in the 0—30 cm layer.